Difusi Inovasi Teknologi Green House di Kalangan Petani Mangga (Studi Kualitatif terhadap Upaya Pengembangan Green House di SKB Situbondo) - Sylva Alkornia (Kanal: Jurnal Ilmu Komunikasi, 2016)
SKB Situbondo was a unit of non-formal education to overcome development of the willingness of community learning to create of a learning society. Innovation from SKB Situbondo was education and training service conducted in one stop service. This research explained how the process of redefining innovation of green house development services and adopting process by mango farmers in the SKB Situbondo area. The type of research was descriptive qualitative. Data collection techniques were done through in-depth interviews, observation, and documentation. Three components of data analysis used are data reduction, data presentation, and conclusion. In addition, to strengthen the results of research used trianggulasi data. The results of research showed that communication channels dominated the diffusion of green house development innovation to mango farmers. Communication was taken place from SKB Situbondo and then transferred to mango farmers. Other channels of communication were group communication, and mass media. Mango farmers in adopting green house development were not all through the stages according to Rogers M Everett in sequence namely knowledge, persuasion, decision, implementation and confirmation. In this study, there were five adopter categories, namely: innovators, early adopters, early majority, late majority, and laggards.